Thecla and medieval sainthood: the Acts of Paul and Thecla in Eastern and Western hagiography - Dabiri, Ghazzal; Ruani, Flavia (Cambridge University Press, 2022)
Explores Saint Thecla and her story as preeminent models for medieval hagiographers across Eurasia and North Africa.